Role of Tacrolimus C/D Ratio in the First Year After Pediatric Liver Transplantation - Prusinskas, Benas; Ohlsson, Sinja; Kathemann, Simone; Pilic, Denisa; Kampmann, Kristina; Büscher, Rainer; Paul, Andreas; Pape, Lars; Hoyer, Peter F.; Lainka, Elke (Frontiers in Pediatrics, 2021)
Background: The calcineurin inhibitor (CNI) tacrolimus (TAC) is a cornerstone agent in immunosuppressive therapy in pediatric liver transplantation (LTX). Adverse effects limit the use of CNI. In adults, calculating the individual TAC metabolism rate allows to estimate the transplant recipient's risk for therapy-associated complications. Methods: A retrospective, descriptive data analysis was performed in children who had undergone LTX in 2009–2017 and had received TAC twice daily in the first year after LTX. A weight-adjusted concentration/dose ratio (C/D ratio) was calculated [TAC trough level/(daily TAC dose/body weight)] every 3 months after LTX to estimate the average individual TAC metabolism rate. Depending on the C/D ratio, all patients were divided into two groups: fast metabolizers (FM) and slow metabolizers (SM). Clinical and laboratory parameters were analyzed as risk factors in both groups. Results: A total of 78 children (w 34, m 44, median age at LTX 2.4; 0.4–17.0 years) were enrolled in the study. FM (SM) had a mean C/D ratio of <51.83 (≥51.83) ng/ml/(mg/kg). FM were younger at the time of LTX (median age 1.7; 0.4–15.8 years) than SM (5.1, 0.4–17.0), p = 0.008. FM were more likely to have biliary atresia (20/39, 51%) compared to SM (11/39, 28%), p = 0.038, whereas SM were more likely to have progressive familial intrahepatic cholestasis (9/39, 23%) vs. in FM (1/39, 3%), p = 0.014. Epstein–Barr virus (EBV) infection occurred more frequently in FM (27/39, 69%) than SM (13/39, 33%), p = 0.002. Three FM developed post-transplant lymphoproliferative disorder. The annual change of renal function did not differ in both groups (slope FM 1.2 ± 0.6; SM 1.4 ± 0.8 ml/min/1.73 m2 per year, and p = 0.841). Conclusions: Calculation of individual, weight-adjusted TAC C/D ratio is a simple, effective, and cost-efficient tool for physicians to estimate the risk of therapy-associated complications and to initiate individual preventive adjustments after pediatric LTX. Lower TAC levels are tolerable in FM, especially in the presence of EBV infection, reduced renal function, or when receiving a liver transplant in the first 2 years of life.